2012
DOI: 10.1021/mp2005164
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrophilic Prodrug Approach for Reduced Pigment Binding and Enhanced Transscleral Retinal Delivery of Celecoxib

Abstract: Purpose Transscleral retinal delivery of celecoxib, an anti-inflammatory and anti-VEGF agent is restricted by its poor solubility and binding to the melanin pigment in choroid-RPE. The purpose of this study was to develop soluble prodrugs of celecoxib with reduced pigment binding and enhanced retinal delivery. Methods Three hydrophilic amide prodrugs of celecoxib were synthesized and characterized for solubility and lipophilicity. In vitro melanin binding to natural melanin (Sepia Officinalis) was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…In our previous report on celecoxib amide prodrugs, we showed that amide prodrugs are metabolized by esterases, amidases, and CYP450 enzymes that are present in both ocular tissues and plasma. 41 Interestingly, we did not observe any significant conversion of the prodrug during in vitro transport study. However, we observed significant conversion during in vivo studies.…”
Section: ■ Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In our previous report on celecoxib amide prodrugs, we showed that amide prodrugs are metabolized by esterases, amidases, and CYP450 enzymes that are present in both ocular tissues and plasma. 41 Interestingly, we did not observe any significant conversion of the prodrug during in vitro transport study. However, we observed significant conversion during in vivo studies.…”
Section: ■ Discussionmentioning
confidence: 58%
“…Although we have not identified the metabolic enzymes involved in bioconversion of prodrug to drug, based on prodrug chemistry we speculate that amidases, CYP450, and esterases are involved in bioconversion of prodrug to drug. In our previous report on celecoxib amide prodrugs, we showed that amide prodrugs are metabolized by esterases, amidases, and CYP450 enzymes that are present in both ocular tissues and plasma …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Formulation-based approaches utilize chemical penetration enhancers [4], prodrugs [5], penetrating peptides [6], and drug delivery carriers such as liposomes [7] and nano-or microparticles [8] to increase drug penetration across these barriers. Physical force-based methods, on the other hand, generally require a physical device, driven by a power generator, to deliver energy to the barriers resulting in transient drug transport enhancement or to physically breach these barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs administered by SCT injection are thought to penetrate into the eye by trans-scleral diffusion [29][30][31], a process that is limited for drugs that are poorly water-soluble [32][33][34].…”
Section: Trans-scleral Transport Of Dsp Compared To Dexamethasonementioning
confidence: 99%